Inquiry on early childhood teachers preparation and retention - Krystyna Nowak-Fabrykowski; Mary Lou Aylor (Problemy Wczesnej Edukacji)
The purpose of this study is to analyze early childhood teacher preparation and investigate the factors that motivated individuals to become early childhood teachers and that have kept them in the profession. This study reports the results of an online survey investigating motives of staying or leaving the early childhood profession. The results of this inquiry point to factors that influenced their choice, taking into consideration their professional preparation. Advice for new early childhood educators just entering the profession is also provided.